2022
DOI: 10.1139/cjfas-2021-0197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating tag-reliant harvest estimators in Chinook salmon mixed-stock fisheries using simulations

Abstract: Management of mixed-stock Chinook salmon fisheries requires balancing fishery access and conservation of vulnerable stocks. Although accurate, timely estimates of stock-specific harvest are crucial in achieving competing objectives, limited numbers of stock assignments (e.g., tag recoveries) can diminish the utility of estimates. We used a flexible simulation approach, applied to both a theoretical and real-world fishery case study, to compare the performance of competing monitoring alternatives and estimators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Historical harvest rates for Sacramento winter Chinook prior to 2000 were reconstructed by O'Farrell and Satterthwaite (2015), and fall Chinook harvest rates were estimated as described in O'Farrell et al (2013). Harvest estimates derived from a limited number of CWT recoveries are inherently uncertain and have become more uncertain over time owing to reduced harvest rates in marine fisheries (Jensen et al, 2022; PSC CTC, 2020; PSC CWT Work Group, 2008); harvest data are also reported as point estimates and do not reflect uncertainty in ERs. While these estimates reliably capture long‐term changes in harvest management, annual estimates of harvest should be interpreted with caution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historical harvest rates for Sacramento winter Chinook prior to 2000 were reconstructed by O'Farrell and Satterthwaite (2015), and fall Chinook harvest rates were estimated as described in O'Farrell et al (2013). Harvest estimates derived from a limited number of CWT recoveries are inherently uncertain and have become more uncertain over time owing to reduced harvest rates in marine fisheries (Jensen et al, 2022; PSC CTC, 2020; PSC CWT Work Group, 2008); harvest data are also reported as point estimates and do not reflect uncertainty in ERs. While these estimates reliably capture long‐term changes in harvest management, annual estimates of harvest should be interpreted with caution.…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of harvest were also compiled for a subset of hatchery reduced harvest rates in marine fisheries (Jensen et al, 2022;PSC CTC, 2020;PSC CWT Work Group, 2008); harvest data are also reported as point estimates and do not reflect uncertainty in ERs.…”
Section: Data Compilationmentioning
confidence: 99%